2013
DOI: 10.1103/physrevlett.111.047002
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Majorana Fermions for Topological Qubits in Superconducting Devices and Cold-Atom Systems

Abstract: We develop an approach to realizing a topological phase transition and non-Abelian braiding statistics with dynamically induced Floquet Majorana fermions (FMFs). When the periodic driving potential does not break fermion parity conservation, FMFs can encode quantum information. Quasienergy analysis shows that a stable FMF zero mode and two other satellite modes exist in a wide parameter space with large quasienergy gaps, which prevents transitions to other Floquet states under adiabatic driving. We also show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
145
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 40 publications
(62 reference statements)
1
145
0
1
Order By: Relevance
“…These modes could be useful for future quantum information applications 48 . Finally, we also showed that this gives rise to a proliferation of Dirac cones in the quasienergy spectrum, a finding which may be useful for simulating static chiral-symmetric Hamiltonians with many Dirac cones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modes could be useful for future quantum information applications 48 . Finally, we also showed that this gives rise to a proliferation of Dirac cones in the quasienergy spectrum, a finding which may be useful for simulating static chiral-symmetric Hamiltonians with many Dirac cones.…”
Section: Discussionmentioning
confidence: 99%
“…Our numerics also reveal that as certain parameters of the ORDKR model are tuned up, a large number of these topological edge modes occurs, together with a proliferation of Dirac cones in the quasienergy spectrum. This finding may be useful for quantum information processing with Floquet Majorana modes 48 and the study of Dirac cones [49][50][51][52][53][54] . So far as we know, this paper is the first to consider weak topological effects in driven systems.…”
mentioning
confidence: 99%
“…An important example is the case of periodically driven one-dimensional topological superconductors, where the bulk Z 2 invariant is replaced by a pair of Z 2 invariants, whose calculation necessitates information beyond that represented by the Floquet Hamiltonian [10]. The edge states then are Floquet Majorana fermions, with potential applications in quantum information processing [11]. Such states, not predicted by the bulk Floquet Hamiltonian, have also been observed in optical realization of a one-dimensional quantum walk [12].…”
Section: Introductionmentioning
confidence: 99%
“…Note that Floquet MMs are a particular class of MMs associated with the Floquet quasi-energy bands of a periodically driven system: 44 they may be used for topological quantum computation as "normal" MMs do. 48 Specifically, we propose to generate multiple Floquet MMs by switching (periodic quenching) a Hamiltonian from H 1 for the first half-period to H 2 for the second one. The Floquet operator U is then…”
mentioning
confidence: 99%